Security and Privacy Issues in IoT Environment - Navod Neranjan Thilakarathne (International Journal of Engineering and Management Research, 2020)
Internet of Things (IoT) is becoming an emerging trend superseding other technologies and researchers considered it as the future of internet. As now the connectivity to the World Wide Web is becoming highly available cost is drastically decreasing so everyone can afford the technology. As Internet of Things provides a great opportunity to develop an important industrial systems and applications with the help of various kind of sensors that can sense out the environment using number of devices that is connected to the internet, usage of IoT is drastically increasing and becoming a common thing. With this sky-rocketed usage and the demand, Communication and storing of the information faces serious security issues as the security of IoT devices become just an afterthought when manufacturing most of the devices. This study tries to summarize this IoT security issues in terms of primary information security concepts confidentiality, integrity and availability with regards to its architecture.